Strategic Challenges: Integrating Marketing Management and Public Policy in Investments in Indonesia Leading up to the 2024 Presidential Election - Frans Sudirjo; Loso Judijanto; Siska Armawati Sufa; Didik Sugeng Widiarto; Iwan Joko Prasetyo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The 2024 Presidential Election in Indonesia is expected to significantly influence the country's investment climate, creating a complex interplay between marketing management strategies and public policy. This study aims to explore the strategic challenges involved in integrating marketing management with public policy, particularly in the context of investment decisions leading up to the election. By utilizing NVivo for qualitative data analysis, this research examines key factors such as governmental policy shifts, investor perceptions, and marketing strategies employed by businesses to adapt to the evolving political landscape. Data was collected from interviews with policymakers, marketing experts, and investors, along with analysis of official documents and media reports. The findings reveal that the integration of marketing management and public policy faces significant obstacles, including regulatory uncertainty and the politicization of investment strategies. These challenges not only affect corporate decision-making but also influence broader economic trends. The study concludes by offering insights into how businesses and policymakers can better align their strategies to foster a more stable investment environment, particularly during periods of political transition. The research contributes to the growing body of literature on the intersection of marketing, policy, and investment in emerging markets.